Efficacy and safety of traditional Chinese medicine as an adjuvant to postoperative chemotherapy in colorectal cancer: a meta-analysis - He, Qinsi; Chen, Xiaodan; Zeng, Haotian; Gao, Xinyu; Zheng, Zhi; Rao, Jun; Wen, Qun; Yu, Xuchao; Zeng, Jiquan (Frontiers in Oncology, 2026)
ObjectiveTo systematically evaluate the efficacy and safety of traditional Chinese medicine (TCM) for postoperative adjuvant chemotherapy for colorectal cancer.MethodsCNKI, VIP, Wanfang, CBM, PubMed, and Web of Science were searched for the randomized controlled trials (RCT) of TCM participating in postoperative adjuvant chemotherapy for colorectal cancer. The search period was from January 1, 2018 to December 31, 2024. Cochrane bias risk assessment tool was used to evaluate the quality of included studies, and RevMan5.4 was used for meta-analysis.ResultsA total of 41 randomized controlled trials involving 2918 patients with colorectal cancer was ultimately included. The results demonstrated that the combination of TCM with chemotherapy was superior to chemotherapy alone in several aspects. These included the objective response rate (ORR), improvement of TCM-related symptoms, levels of tumor markers CEA and CA199, immune function indicators (CD3+, CD4+, CD4+/CD8+, NK cells), and quality of life as measured by the KPS score. Additionally, the combination therapy reduced CD8+ levels and mitigated abnormal laboratory indicators caused by chemotherapy, such as leukopenia, thrombocytopenia, decreased hemoglobin, and abnormal liver and kidney function. Furthermore, it alleviated chemotherapy-related adverse effects (AEs), including nausea, vomiting, and peripheral nerve toxicity.ConclusionsTCM may be associated with improvements in quality of life and reduce chemotherapy side effects in postoperative colorectal cancer patients, though large-scale rigorous trials are needed to confirm efficacy and safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025635900.